Evaluation of Ovarian Radiation Dose from Internally Scattered X-rays in Posteroanterior (PA) Chest Radiography With and Without Contact Gonad Shielding: Phantom Study - Mat Lazin, Siti Nur Atiqah; Sayed, Inayatullah Shah (International Journal of Allied Health Sciences, 2024)
Background: Scattered radiation originating from the patient's body disperses unevenly in multiple directions, posing a risk of incidental exposure to radiosensitive organs, such as the ovaries, which may absorb radiation from internally scattered X-rays. Although external radiation shielding is a common practice, internal scatter from within the patient presents additional complexities. This study aimed to quantify the radiation dose received by the ovaries using optically stimulated luminescence dosimeters (OSLDs) in posteroanterior (PA) chest X-ray examinations, both with and without the application of a contact gonad shield. Methods: A Siemens Multix Top X-ray imaging system was utilized for this study, operating with tube voltages between 70 kVp and 100 kVp and employing Automatic Exposure Control (AEC). The source-to-image distance (SID) was consistently maintained at 180 cm. The entrance skin dose (ESD) measurements corresponding to the ovaries were conducted using nanoDot OSLDs. These were positioned within the RANDO phantom at slice 29 to align with the anatomical location of the ovaries. Measurements taken with and without the use of a contact gonad shield. Results: The recorded ovarian ESD with contact gonad shielding averaged 2.2, 2.4, 3.7, and 3.0 mGy at 70, 80, 90, and 100 kVp, respectively. In contrast, without contact gonad shielding, the average ovarian ESD observed at 1.0, 1.8, 2.6, and 3.1 mGy at the respective tube voltages. Radiation dose (ESD) by each ovary varied based on the kVp and the use of contact gonad shielding. Results indicated an unexpected increase in ovarian dose with the use of a contact gonad shield, and a consistent rise in ESD noted with increasing kVp, irrespective of shielding. Conclusion: Scatter radiation in radiography presents a risk to organs beyond the primary imaging area, particularly the ovaries in PA chest radiography. Research indicates that higher tube potentials result in increased ESD to the ovaries. Interestingly, contact gonad shielding, a conventional method to reduce exposure, may not significantly lower radiation exposures and could potentially increase dose to ovaries. Therefore, discontinuing contact gonad shields seems justifiable for radiation safety. Optimization of tube voltage and tight collimation are crucial for minimizing ovarian radiation exposure.